MARKETING COMMUNICATIONS AND THEIR ROLE IN IMPROVING THE MENTAL IMAGE OF TOURISM COMPANIES - Prof. Dr. Alaa Abd Al Hussein Radhi; Noor Qasim Khazim (Scholars Digest Publishing, 2023)
This study aimed to determine the level of relationship between marketing communications and the mental image of travel and tourism companies, and its importance emerged in the extent to which these companies adopt marketing communications as they contribute to improving the quality of service provided to customers. The research community was represented in the travel and tourism companies in the holy city of Karbala, while the research sample was represented by the managers of these companies. A field study was carried out on the practical side using the questionnaire form, and a set of statistical methods were relied upon to analyze the sample answers, which are (the arithmetic mean, standard deviation, relative importance). In customer satisfaction, and this means that it has an impact on improving the mental image of travel and tourism companies. A set of recommendations has also been reached, the most important of which is the need to increase attention to marketing communication technology in order to raise the level of tourism and travel companies and pay attention to the desires of the tourist and work to meet them.
Keywords: Marketing Communications, Mental Image, Tourism Companies.